When Hatred Dies - San Jose State Normal School:::::::::
The poem, "When Hatred Dies," by R.F. Eberhart appears in the 1915 Senior Yearbook. Eberhart was involved with the San Jose State Normal "Peace Society." (San Jose State La Torre, 1915 Senior Yearbook)